Understanding The Mimicker: Epidemiological Pattern and Determinant of Melioidosis Mortality in Negeri Sembilan, Malaysia. - Shahrul Azhar Md Hanif; Mohd Rohaizat Hassan; Muhammad Ridzwan Rafi'i; Ahmad Farid Nazmi Abdul Halim; Mohd 'Ammar Ihsan Ahmad Zamzuri; Muhammad Ismail; Siti Salwa Ibrahim; Massitah Mihat; Lokman Rejali; Muhammad Habiruddin Zubir; Muhammad Salihin Mahadi; Shazwanis Ahmad Ismail; et al. (Public Library of Science (PLoS), 2024)
Background Melioidosis, a tropical infectious disease caused by Burkholderia pseudomallei, is epidemic in most region in Southeast Asia with high case fatality. However, there is scanty information regarding the disease's epidemiological pattern, demographics, and underlying risk factors. Method This 5-year retrospective study of 185 confirmed cases which were taken from the Negeri Sembilan Melioidosis Registry between 2018 and 2022. We aim to describe the incidence, mortality rate, case fatality, relationship with meteorology, and factors that influence mortality in this central region of Peninsular Malaysia. Results Incidence rate (IR) of melioidosis in Negeri Sembilan is varied at 1.9 to 5.1 with mean of 3.1 in 100,000 population per year. IR varied between districts in the state from zero to 22.01 in 100,000 population per year. Mortality rate were ranged from 0.17 to 0.74 cases with mean of 0.44 cases in 100,000 population per year. The case fatality rate of this state scattered from 8.70% to 16.67%. There were no significant linear associations between cases and deaths with monthly rainfall and humidity. The mean age of patients was 52.8 years, predominated with age around 41-60 years old. Males (77.8%) predominated, and the majority of cases were Malays (88.9%) and had exposed to soil related activities (74.6%). Mortality from melioidosis was more likely in Bumiputera and non-Malaysians (p<0.05). Patients who had at least one comorbidity were at a higher risk of death from melioidosis (p<0.05). Diabetes mellitus was found in 41.1% of all identified cases, making it a major underlying risk factor for both developing and dying from melioidosis (aOR:19.32, 95%CI:1.91-195.59, p<0.05). Hypertension and mortality status in melioidosis are also significantly correlated (aOR: 7.75, 95% CI: 2.26-26.61, p<0.05). Conclusion The epidemiological patterns of cases reported from Negeri Sembilan are consistent for the most part from previous studies in other states in Malaysia and global with regard to its incidence, case fatality, demographic and predisposing chronic diseases. Diabetes mellitus and hypertension were significantly linked to increased mortality among all determinants.